The institutional background of local sustainability strategies - Baják, Imre (Acta Agraria Debreceniensis, 2008)
The system of local sustainability strategies is shaped by the intentions of the central government and local initiatives together. From the aspect of the hierarchy of government organization in Hungary it means that there are institutions on the central government’s side – different ministries or other governmental institutions – the role of which is mainly coordination; and local governments (regional and local as well) also form their institutions at the municipality. It is important to examine the institutional background, as in Hungary the formation of sustainability policy is still in its infancy, so it is well worth taking the institutional background of countries the circumstances of which are similar to ours and have successful sustainability policies as a basis. In this presentation I will examine whether the top-down or the bottom-up approach is chosen, which institution is in charge of the process, what the legal background is like, and what sources are available for use in these countries.